Strategi Mahasiswa dalam Menyelesaikan Tugas Perkuliahaan di Jurusan Bimbingan Konseling Pendidikan Islam - Melisa Febriani; Dinda Aulia; Arlina Arlina (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to determine the strategies of students in the Islamic education counseling and guidance department in completing course assignments. The method in this research uses qualitative methods. Qualitative methods are research approaches that aim to understand human phenomena in an in-depth and descriptive way, this involves collecting data and figures, such as text, images, sounds, or videos, and analyzing them to identify patterns, themes, and meaning. The results of this research found that students of the Islamic Counseling and Guidance Study Program at the Faculty of Tarbiyah and Teacher Training have their own ways and strategies for completing course assignments, even though overall they have not been able to complete assignments on time or often postpone them. This research is expected to have a positive impact on students majoring in Guidance. Islamic education counseling in completing lecture assignments and developing their knowledge regarding strategies for completing lecture assignments.